2017
DOI: 10.1016/j.psyneuen.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, inflammation and treatment response in major depression

Abstract: Objective Increased inflammation and oxidative stress have been shown in Major Depressive Disorder (MDD), although there is significant heterogeneity across studies. Whether markers of inflammation and oxidative stress are associated with antidepressant treatment response in MDD is currently unclear. The goals of the present study are to investigate markers of inflammation and oxidative stress in unmedicated MDD subjects and controls and test the relationship between these markers and antidepressant response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
233
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 358 publications
(264 citation statements)
references
References 51 publications
8
233
3
3
Order By: Relevance
“…However, our finding is in line with a previous report from our group that GSH levels were not decreased in MDD subjects compared to healthy controls, despite the fact that F2-isoprostanes were elevated (Lindqvist et al, 2017). Our findings may indicate that chronic oxidative stress results in a compensatory but inadequate increase in GSH synthesis in attempt to reduce further oxidative damage (Andreazza et al, 2009), but this is purely hypothetical.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…However, our finding is in line with a previous report from our group that GSH levels were not decreased in MDD subjects compared to healthy controls, despite the fact that F2-isoprostanes were elevated (Lindqvist et al, 2017). Our findings may indicate that chronic oxidative stress results in a compensatory but inadequate increase in GSH synthesis in attempt to reduce further oxidative damage (Andreazza et al, 2009), but this is purely hypothetical.…”
Section: Discussionsupporting
confidence: 94%
“…Oxidative stress data from subsets of this sample have been previously reported in relation to hypotheses not explored in the present study (Lindvist et al, 2017; Rawdin et al, 2013). MDD diagnoses were determined using the Structured Clinical Interview for the DSM-IV (First et al, 1997).…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…In previous studies, the oxidative and nitrosative stresses have been widely reported to be involved in the pathogenesis of depression . Here, we studied the influence of TUDCA on NO, MDA, and GSH.…”
Section: Resultsmentioning
confidence: 97%